Emotional Intelligence and Age as Predictors of Managerial Effectiveness among Bankers in Anambra State, Nigeria - Ifeanacho, Nnaebue Collins; Nneamaka, Anazodo Nkechi; Chinaemerem, Ogbonna Goodness (Social Science Research, 2024)
This study investigated emotional intelligence and age as predictors of managerial effectiveness among bankers. The participants of the study were 104 bank managers that comprised of 78 males and 26 females drawn from four major cities (Awka, Ekwulobia, Nnewi & Onitsha) in Anambra State, Nigeria. The participant’s age ranged from 41 to 55 years with mean age of 36.44, and standard deviation of 6.89. Simple random sampling technique was used for the selection of the banks, while purposive sampling was used to select the participants. Instruments used for the study were Indigenous Emotional Intelligence Scale, and Managerial Effectiveness Scale. The design of the study was Correlational design while Multiple Linear Regression statistics was used for analysis. The results showed that some dimensions of emotional intelligence like interpersonal skill at (F7, 218), β= .27**, p<.05, problem solving, at (F7, 96), β= .30**, p<.05, flexibility at (F7, 96), β= .70**, p<.05 and optimism at (F7, 96), β= .99**, p<.05 significantly predict managerial effectiveness, while assertiveness at (F7, 96), β= -.79**, p<.05 had negative prediction on managerial effectiveness, and empathetic response, at (F7, 96), β= -.03, p>.05, and stress tolerance, at (F7, 96), β= .07, p>.05 had no prediction on managerial effectiveness; Age at (F7, 96), β= .08, p<.05 had significant prediction on managerial effectiveness. It further revealed that emotional intelligence dimensions accounted for 88.9% of the managerial effectiveness, with R = .889, R2 = .790, adjusted R2= .783, (F7, 96) = 116.95, p<.05. Based on the findings, it recommends that Bank owners and senior management should develop training programs for managers where some aspects of emotional intelligence could be learned in order to make them better leaders and this in turn, will definitely lead to much effectiveness and quality performance from the managers.